Estrutura etária e crescimento econômico: evidências no Rio Grande do Sul/Brasil (1991-2010) - Lauana Rossetto Lazaretti (El Colegio Mexiquense, A.C., 2018)
The aim of this study is to analyze the relationship between the change in the age structure and the economic growth in Rio Grande do Sul from the Demographic Census of 1991, 2000, and 2010. Spatial econometric models are used. The demographic variables were significant for the convergence of per capita income. The increase in population density and the quality of life of the population contribute to economic growth. The absolute population growth lowers per capita income, while the age group of people aged between 35 and 45 years are those that contribute the most to the increase in income.